How Countries Can Fully Implement the New York Convention: A Critical Tool for Enforcement of International Arbitration Decisions - Forneris, Xavier; Mocheva, Nina (In Focus, 2019)
The year 2018 marked the 60th anniversary of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, the most important international convention in the area of international commercial arbitration. The Convention is also said to be the most successful international treaty in the area of private international law. This note primarily targets policy makers and their legal advisors in countries looking at ways to improve their business environment, to become more attractive locations for trade and investment, through better dispute resolution options for international transactions. First, the note explains that international commercial arbitration, as part of countries' legally recognized dispute resolution options, is critical to cross-border contract enforcement. As countries strengthen their international arbitration regimes, they improve their competitiveness in international markets and increase investment and trade by reducing transaction risks and the cost of new infrastructure projects. Countries can improve their international commercial arbitration systems by passing modern legislation consistent with international best practice, ratifying international arbitration conventions, strengthening judicial capacity to enforce arbitral awards, and investing in local arbitration centers.

The Recovery of Debts Inherent in Cheques without Cover in Cameroon via the OHADA Simplified Recovery Procedure and Enforcement Measures - Penda, Akama Samuel; Ndikum, Nji Keneth (International Journal of Trend in Scientific Research and Development, 2019)
The vast number of commercial transactions that take place daily in the modern business world will be inconceivable without negotiable instruments like cheques. This is the reason why the recovery of debts inherent in cheques without cover has been given the attention it deserves within the CEMAC Region under the OHADA Uniform Act on Business Law. The OHADA Uniform Act on Simplified Recovery Procedure and Enforcement Measures has instituted a procedure in the member states of the OHADA zone to recover debts of a company when it eventually goes bankrupt or when it winds up. It should however be understood that all the member states of CEMAC are OHADA signatories. This ipso facto means that Cameroon being a member of CEMAC, with its bi jural nature, where the Common Law and Civil law legal systems operates in the Former West Cameroon and Former East Cameroon respectively, both parts of the country are bound to implement the OHADA Uniform Act in their various jurisdictions. The Uniform Act on Simplified Recovery Procedures and Enforcement Measures was issued on the 10th of April 1998. Like the Uniform Act on Securities, this Act overlaps the bound of pure business law in that it effects a general reform of civil procedure in relation to recovery and enforcement. The reform was indispensable of the OHADA Member States, only Mali had, in 1994, put in place a modern system that was suited to present day economic and social conditions. Otherwise, the relevant legislation dated, at best from the 1970s and in several cases from colonial times. The OHADA Uniform Act governs commercial companies and Economic Interest groups. Since banks are commercial companies governed under Public Limited Companies S. As , they are equally governed by the OHADA Uniform Act. Thus, this paper questions the potentials of the OHADA Simplified Recovery Procedure and Enforcement Measures in relation to the special mechanisms for the Recovery of Debts inherent in cheques without cover in Cameroon.
Keywords: Chèques; Procédure simplifiée; Recouvrement de créances; Recovery of Debts; Voies d'exécution

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Personal Property Security Law: International Ambitions and Local Realities - Castellano, Giuliano; Tosato, Andrea (International Business Law, 2019)
Personal property security law is a key element of “access to credit” and “financial inclusion”. The prevailing view is that a legal framework enabling the effective use of personal property as collateral markedly benefits both lenders and borrowers. Lenders can offer financing at a lower cost thanks to reduced credit risk; borrowers can access funding by leveraging the otherwise unavailable value of the assets integral to their operations. Over the past century, the priorities of personal property security law have evolved fundamentally. As small and medium-sized enterprises (SMEs) and individual entrepreneurs have become the growth engine of both developed and developing economies, legislators have grown sensitive to the financing needs of these entities. In parallel, the advent of the information society has demanded that lawmakers address squarely the rules governing the use as collateral of intangibles such as “receivables”, “intermediated securities”, “non-intermediated securities”, and “intellectual property rights”, rather than confine their gaze to tangibles such as industrial machinery, mobile equipment and inventory. Concurrently, the increasingly transnational nature of both economic development policies and commercial activity have engendered the need for global principles and standards for asset-based lending. To address these novel priorities and promote a healthy and vibrant credit ecosystem, international and regional organizations have undertaken projects aimed at modernizing and harmonizing personal property security law. Over time, these efforts have yielded a panoply of legal instruments. Binding conventions have been adopted to unify the rules of discrete facets of personal property security law, while soft-law texts, such as model laws and legislative guides, have been formulated to supply comprehensive legal templates to lawmakers keen to revise their domestic legal regimes. Nevertheless, states have struggled to assimilate these international efforts into their domestic legal systems. Common law jurisdictions have been loath to abandon the familiarity and safety of the path paved by centuries of case law; in similar vein, civil law jurisdictions have resisted inducements to renovate the normative infrastructure erected by the codifications of the 19th century. This Chapter explores the tension between international ambitions and local realities, with a special focus on the issues encountered in civil law jurisdictions. To this end, the case of Italy is examined as a living experiment in comparative personal property security law. In this jurisdiction, the recent enactment of a non-possessory security device, absent a comprehensive reform of the country’s civil code affords important lessons for any civil law system which might be pondering personal property security law reforms. More profoundly, it epitomizes the gap that separates the aspirations of international legal instruments from their effective implementation in domestic contexts. This analysis is divided into two parts. The first reviews international and regional legal initiatives that have shaped the personal property law landscape and then identifies a set of core tenets shared among them. In the second part, attention shifts to Italy, scrutinizing both the personal property security legal edifice originally constructed in this jurisdiction and the attempts to overhaul it that have taken place over the past three decades. This is followed by a critical appraisal of the current state of the law, by reference to the aforementioned core tenets of personal property law reform.
Keywords: Commercial Law; Law Reform; Non-possessory Pledge; Personal Property Security Law; Secured transactions

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

The contribution mediation can make in addressing economic crime in corporate and commercial relationships in South Africa - Hoffman, Cornelia Hendrina (Stellenbosch University, 2019)
Economic crime is complex and costly. It is costly because it harms victims, both directly and indirectly, as well as the broader economy. The cost is not only financial, but also to confidence and trust in corporate and commercial relationships in South Africa. Economic crime is complex because it includes offences from common-law fraud to statutory contraventions such as incorrect bookkeeping. There are several mechanisms in the South African legal justice system to address economic crime. The conventional legal models include adversarial criminal prosecution of the offender and civil compensation claims, the model of inquisitorial administrative investigations and sanctions like penalties and compensation orders. In 2001 section 105A of the Criminal Procedure Act, namely plea and sentencing agreements, was added as a model of negotiated justice. This mechanism allows the prosecution and the offender to negotiate and enter into an agreement regarding the charges and the sanctions, subject to approval of the court that the plea of guilty is proper and that the proposed sanction is a just sentence. This dissertation proposes that mediation be added to the existing alternative models to help combat economic crime. Mediation involves negotiated justice, as well as restorative justice. More specifically, mediation as a restorative justice process, constitutes a practical alternative to standard litigation as the affected parties themselves, with the facilitation of a third person, resolve the disputes between them. Mediation, a facilitative and flexible procedure, allows the voices of both the victim and the offender to be heard securely and meaningfully. Mediation is rehabilitative and allows for agreed restorative provisions for both the perpetrator and the victims of economic crime. The outcome is a proposed amendment to the Criminal Procedure Act 51 of 1977, namely the insertion of section 105B, “Mediated Settlement Agreements”, that will provide for mediation and a mediated settlement agreement to be incorporated into and form part of the criminal justice processes. It is envisaged that an accredited mediator will mediate between the parties, including the public prosecutor, the perpetrator, the victim and possibly members of the community. The mediated settlement agreement will include both compensation for the victims and a proposed sentence for the perpetrator. This mediated settlement agreement will then be tabled before the court for adjudication and approval to serve as an effective court order. The proposal is a logical legal development of section 105A of the Criminal Procedure Act on plea and sentencing agreements, as the process of mediation builds on the process of negotiation established in it. To put it bluntly, if a plea and sentence agreement can be negotiated between the prosecutor and the offender, a plea and sentence agreement can be mediated between the prosecutor, the offender and the victim. Mediation can integrate and expand the constitutional principles of reparation and ubuntu and curb economic crime by providing an effective restorative and just response to it.
Keywords: Alternatives to prosecution; Commercial law; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; South Africa

Multidimensionality of Sustainable Public Procurement (SPP) - exploring concepts and effects in Sub-Saharan Africa and Europe - Stoffel, Tim; Cravero, Carol; La Chimia, Annamaria; Quinot, Geo (Sustainability, 2019)
Strategic objectives in public procurement, such as environmental or social considerations, are being increasingly referred to under the umbrella term of sustainable public procurement (SPP). The concept of sustainability is intrinsically multidimensional, encompassing environmental, social, and economic aspects. However, the existing literature on SPP highlights the generalization that the regulation and practices of public procurement are biased toward the environmental dimension. There is conflicting evidence from countries in Sub-Saharan Africa (SSA) that calls for further investigation. Analyzing how SPP is actually constituted in SSA and contrasting it with the situation in the European Union (EU), as a spotlight on the Global South and North, contributes to a better understanding of sustainability in public procurement. The comparative analysis will help with understanding processes related to the integration or disintegration of sustainability dimensions in SPP. Our results indicate a contrary orientation on the environmental and the social dimensions in the EU and SSA. Although there is no sign of a comprehensive integration of all dimensions in SPP, there are developments toward the integration of the ‘missing’ dimension in the respective regional setting. Thus, at the moment, achieving a multidimensional implementation of SPP appears to be more a matter of expanding SPP practices of the ‘missing’ dimension than of pushing for integrated concepts.
Keywords: GPP; Government purchasing; Green public procurement; Multidimensional sustainability; SRPP; Socially responsible public procurement; Socioecological transformation; Sustainable development; Sustainable supply chains

The Influence of IAS/IFRS on the New OHADA General Chart of Accounts - Tchokoté, Ivan Djossa (Journal of Modern Accounting and Auditing, 2019)
Accounting standardization in black African French-speaking countries is presented through two streams of research. The first stream presents the general chart of accounts common to all these countries as an accounting model which reconciles the divergences between the Anglo-Saxon and continental approaches to accounting, and thereby satisfies the requirements of users of accounting information. The second stream considers that the convergence towards IAS/IFRS is a vital way of attracting international investors and increasing development. This article stands by the second perspective and analyzes the changes introduced in the PCG-OHADA (2017) compared to the PCG-OHADA (2000). It shows that the new provisions of the PCG-OHADA are mainly inspired by IAS 1, IAS 16, IAS 19, IAS 36, IAS 38, IAS 40, and IFRS 6.
Keywords: Accounting harmonization; Accounting standards; IFRS; PCG

A comparative appraisal of debt relief measures for no income no assets (NINA) debtors in Nigeria - Osunlaja, Tobi Titilayo (University of Pretoria, 2019)
Nigeria currently has a non-functioning insolvency system; it is yet to record a successful insolvency case. This failure principally is attributable to the weak laws and enforcement policies in existence. The problem is exacerbated by burgeoning consumer debt in the formal sector. The causal factors for this increase in debt are negative economic growth indices such as rising inflation, interest rates and unemployment. With these indices predicted to worsen, a new Bankruptcy and Insolvency Act (BIA) was proposed in 2016. The BIA seeks to regulate individual insolvency proceedings in Nigeria. However, the BIA (as currently conceptualized) does not make provision for debtors with neither income nor assets, often referred to as No Income No Assets (NINA) debtors who, it can be argued, are in the majority in the Nigerian state. The aim in this thesis is to propose debt relief measures that cater for NINA debtors in Nigeria. This proposal aims to prevent further discrimination against these debtors in terms of the current law and the proposed BIA. It envisages that catering for NINA debtors in Nigeria will boost the Nigerian government’s drive to encourage entrepreneurship. In providing for NINA debtors it will provide a safe landing for poor debtors in the event of entrepreneurial failure. The thesis achieves its stated aim by studying international principles and guidelines as espoused by leading bodies. Furthermore, the thesis performs a comparative analysis of relevant NINA provisions in South Africa, Sweden, France, Ireland and Canada. The thesis proposes amendments to the proposed BIA in light of the aforementioned analysis and posits that procedures that are formal and extra-judicial, which have no financial requirements and are easily accessible to debtors should be incorporated.
Keywords: Debt relief measures; Insolvency; Insolvency system; Laws and enforcement policies; No Income No Assets (NINA)

Problems of Enforcement of ICSID Awards: An Analysis of Micula Case - Hasankhani, Ali (Public Law Researsh, 2019)
In the case Micula A.O. v. Romania, the arbitration tribunal established under the auspices of the International Center for Settlement of Investment Disputes (ICSID) sentenced Romania to pay a compensation for the revocation of investment incentives and for the breach of fair and equitable treatment principle that had been laid down in a bilateral investment treaty between Sweden and Romania. Considering investment incentives as a breach of the EU regulations regarding state aids, the European Commission then rendered a directive, prohibiting the enforcement of the arbitration award by the member states. As articles 53 and 54 of ICSID emphasize that the awards are binding, the EU Commission’s act of rendering the aforementioned directive, and the member states refusal to comply with the award equals to giving the EU law primacy over international law, which should be considered as a breach of their international obligations. Using a descriptive-analytical method, this article seeks to explain the viewpoints of the parties and the courts which were asked to enforce the award, as well as to determine the nature of their acts.

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

What Process is Due – Sanctions Regimes of Multilateral Development Banks - Madir, Jelena (University of Westminster, 2019)
Much has been written about the consequences for companies of criminal convictions for bribery and other corrupt practices. However, less attention has been paid to the sanctions regimes that have been developed by multilateral development banks in order to combat fraud and corruption in their operations. This is likely to change in view of the fact that on 9 April 2010, the heads of five leading multilateral development banks (MDBs) – the African Development Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the Inter-American Development Bank and the World Bank Group – signed the Agreement for Mutual Enforcement of Debarment Decisions, which provides for mutual and reciprocal enforcement of debarment decisions taken by any one of them against parties that engage in fraud, corruption, coercion or collusion in connection with MDB-financed projects. For parties that are seeking financing form an MDB or are competing for contracts funded by an MDB, this means that a sanctionable practice committed in a single country could result in global sanctions. Against this background, this thesis examines the type of due process rights that should characterise MDBs’ sanctions procedures. More particularly, the thesis analyses the extent to which MDBs’ sanctions regimes should be bound by the rules of law, analogous to those of national judicial bodies, and the level of due process and transparency that should be required from these ever-evolving regimes. In other words, (how) can the tension between the administrative and business considerations of MDBs’ sanctions regimes (coupled with their immunity from judicial review) be reconciled with due process considerations and principles of fairness that underpin a national judicial model?

Block Chain Accounting: The Face of Accounting and Auditing in Industry 4.0 - Antoney, Laly; Augusthy, Theresa Josephine (International Multilingual Journal of Science and Technology, 2019)
Keywords: Accounting Education; Block Chain Accounting; DLT; Future Audit; Tripple Entry Book Keeping

The power of will and choice of law in international contracts - Dazzi, Pietro Giulio (LUISS Guido Carli, 2019)
Party autonomy and sovereignty. Historical developments on party autonomy, the evolution of choice of law. The freedom of choice. The freedom not to choose, absence of choice. Limits to the freedom of choice. Limits to the freedom of choice, an expression of sovereignty. Same functions, different results.

A critical analysis of the effectiveness of the business rescue regime as a mechanism for corporate rescue - Bagwandeen, Kiren Kesh (University of KwaZulu-Natal, 2019)
Almost eight years after the enactment of the business rescue regime under the Companies Act 71 of 2008, and a plethora of judgments which have probed and prodded its provisions, it is an opportune time to ascertain whether the business rescue regime is an effective corporate rescue mechanism suitable to the modern day demands of the South African economy. In the current economic downturn, South Africa can ill afford a repeat show of the failed judicial management system. It requires a modern and effective corporate rescue mechanism that can be utilised in appropriate circumstances as a viable alternative and not merely a precursor to liquidation. This dissertation seeks to provide a critical analysis of the effectiveness of the business rescue regime to ascertain its worthiness as a corporate rescue mechanism.
Keywords: Bankruptcy; Business failures; Corporation law; Insolvency; South Africa

Proceedings of 1st Annual Research Symposium on International Commercial Arbitration - Casoria, Maria (Royal University for Women, 2019)
Keywords: Arbitrage; Arbitragem; Arbitration; Convention on the Recognition and Enforcement; Foreign Arbitral Awards; International Commercial Mediation; International Settlement Agreements; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements; UNCITRAL Model Law

The Legal Regime of Real Estate Investment Financing by Musharaka Contract - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

Causes of Delay in the Resolution of Commercial Disputes via Litigation Arbitration as a Way out within OHADA Laws - Sigala, Buma Roland (International Journal of Trend in Scientific Research and Development, 2019)
An essential requirement of justice is that it should be dispensed as quickly as possible. It is a well-known adage that, « justice delayed is justice denied». Delay in litigation is caused by a number of factors. For example in litigation the parties have the right to make a counterclaim, right to make appeal etc. Arbitration has been able to overcome the factors which cause delay in litigation because in arbitration, parties are given the right to exclude the possibility to make a counterclaim, the right to make appeal has expressly been prohibited by the Organization for the Harmonization of Business Laws in Africa (OHADA)1 legislator etc. But since the OHADA legislator has not expressly prohibited counter claim in arbitration, it is recommended that counterclaim should be expressly prohibited in arbitration as it is the case with appeal. This article aims at identifying the causes of delay in the disposal of commercial disputes via litigation and how these causes of delay have been combated in arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; Delay commercial; Disputes Litigation; Law and management

Electronic Tax System As A Panacea For Tax Revenue Leakages In Nigeria - Nwamgbebu, Obinna; Oketa, Chiamake; Odom, Amarachi; Nwambe, Cynthia; Nweke–Charles, Uchenna (African Journal of Politics and Administrative Studies, 2019)
The broad objective of the study is to assess the problems of the traditional tax system in Nigeria and establish electronic taxation as a solution to these problems. The study adopted content analysis in analyzing text books, journals, newspapers and other essential materials that were used to obtain the needed information for the study. Extensive review of the literature showed that electronic tax system solves the problem of low tax collection, unavailability of tax statistics and poor record keeping, complex of payment and high cost of tax compliance. The implication of these findings is that an adoption of electronic tax system is an intelligent means of achieving a system of tax administration that allows for the collection and accountability of required taxes at a minimum cost. The study concluded that there are some challenges with the manual system of administering taxes and that modern technology could simplify these challenges and alienate them in the form e-tax. The study therefore recommended that government should support with everything on their disposal the establishment of e-tax administration so as to start ripping the benefit of high rate of compliance among taxpayers at all levels of government in Nigeria.

Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.

Adoption, compliance, and consequences of International Financial Reporting Standards in Africa - Tawiah, Vincent K. (Griffith University, 2019)
This thesis investigates the adoption, compliance and consequences of International Financial Reporting Standards (IFRS) in Africa, a continent which has mostly been ignored in prior studies due to the use of generic proxies. Drawing on DiMaggio and Powell (1983), this thesis examines the institutional pressures of IFRS adoption in Africa. Stakeholder salience theory, developed by Mitchell, Agle and Wood (1997), is employed to analyse the determinants of IFRS compliance outside the traditional capital market settings. As regards to the consequences of IFRS in Africa, this thesis analyses the impact of IFRS on audit fees, audit reporting lags and auditor switch. The study used panel data from 54 countries and 205 firms covering the financial years 2003-2016. Secondary data was sourced from reputable database and annual reports of sample companies. Different analytical tools such as ordinary least squares, logit and multinomial regressions were used based on their suitability to address the research questions. The study found that only 18 out of the 54 countries required all listed and large companies to report per IFRS, while 25 did not permit IFRS. The results supported the theoretical prediction that coercive, mimetic, and normative isomorphism influenced IFRS adoption in Africa. Specifically, the World Bank (WB) and International Monetary Fund’s (IMF) influence on African countries in adopting IFRS was not through foreign aid and grants; instead, their recommendations made in the Report on Observance of Standard and Codes (Accounting and Auditing) initiatives. The finding(s) also demonstrated that the presence of global audit firms and the number of years of IFAC membership had a strong association with a country’s decision to adopt IFRS. Moreover, countries with strong professional accounting organisations (PAO) were more likely to adopt IFRS. On IFRS compliance, the study found that the average compliance score among the companies over the period was 70.94%, with a minimum score of 58.59% and a maximum of 83.55%. The findings reported a significant positive association between audit committee competence (ACC) and compliance, and between chartered accountants on board (AOB) and compliance. The thesis also documented that compliance has been increasing over the years. Regarding the impact of IFRS on the audit market, the findings suggested IFRS was positively and significantly associated with an increase in audit fees regardless of early or late adoption. Also, on average, ARL increased by 26% across all samples, with late adopters experiencing 28% and earlier adopters 22% during the adoption year. Contrary to the late adopters, early adopters experienced a significant increase in audit fees during the pre-IFRS period due to the set-up and implementation at the time. In addition, IFRS adoption was likely to cause companies to switch from small audit firms to the Big 4. The findings on adoption suggest that global accounting agencies such as IFAC and IASB should focus on building vibrant national level accounting institutions such as PAOs to facilitate the adoption of IFRS in Africa. The thesis, therefore, adds to the adoption literature the finding that the isomorphic pressures in Africa are different from those suggested in prior studies. The results on compliance imply that companies that appoint more professional accountants to their boards are more likely to comply with the requirement of IFRS. Therefore, it is suggested that companies should engage more chartered accountants in their governance. Also, corporate boards must strive to strengthen their audit committees by appointing more NEDs and CAs to the committee. The findings also provide valuable information for professional accounting organisations on the role of its members (professional accountants) in the effectiveness of IFRS compliance. The findings of the consequences of IFRS on the audit market alert small and medium practitioners (SMPs) in non-IFRS countries of the possible loss of clients to the Big4 due to the adoption of IFRS. To mitigate this effect, the national PAO should build the capacity of their local accountants through training and education to handle the complexities and continuous upgrading of IFRS. Such training is seen as being crucial for SMPs in OHADA countries, Ethiopia, Djibouti and other countries which are in the process of implementing IFRS.
Keywords: Adoption; Africa; Audit market; Compliance; Consequences; IFRS; Institutional pressures; International Financial Reporting Standards; Stakeholder salience

What the African Continental Free Trade Agreement Protocol on Dispute Settlement says about the culture of African States to Dispute Resolution - Akinkugbe, Olabisi (Articles, Book Chapters, & Popular Press, 2019)
An effective Dispute Settlement Mechanisms (DSM) upholds a rules-based trade regime; enunciates, clarifies and develops the jurisprudence of its constituent trade agreement; and also ensures predictability in the trading regime. Article 20 of the African Continental Free Trade Agreement (AfCFTA) establishes the DSM. The AfCFTA Protocol on Dispute Settlement (“Dispute Protocol”) provides for the rules and procedures for the settlement of disputes. Unlike the majority of the African regional economic community courts that are modelled after the Court of Justice of the European Union, the AfCFTA-DSM follows a handful of other regional judicial bodies – such as the Southern African Community Development Community (SADC) and the Tripartite Free Trade Area Agreement (TFTA) – that are modelled after the World Trade Organization (WTO) dispute settlement mechanism.
Keywords: AfCFTA; Dispute Settlement Mechanisms; Free Trade; Trade Agreement

The models of attribution in the establishment of corporate liability revisited - Heese, Francisca Alida (Stellenbosch University, 2019)
The separate legal personality of a company is one of the cornerstones of modern corporate law. Nevertheless, due to the artificial nature of a company it has no inherent moral blameworthiness necessary to impose corporate liability. With a rise in corporate wrongdoing, there is a need to hold companies liable. Therefore, certain models of attribution have developed whereby the conduct and will of a corporate actor can be imputed to the company to establish corporate liability. Especially in the realm of corporate criminal liability, these models of attribution have played a pivotal role to establish corporate wrongdoing. The two broad theories underlying the models of attribution are the fiction and realist theories respectively. The directing minds doctrine or identification doctrine and the vicarious liability model are traditionally associated with the fiction theory, which is rooted in the abstract nature of a company. Whether the traditional models of attribution are suited for complex modern organisational structures, is explored in this thesis, whilst a more functional and realistic approach to corporate liability is proposed. Often the question of “what is a corporation” has overshadowed the determination of corporate liability, thus a more contextual analysis based on law and economics is proposed to ensure corporate liability. The development of the rules of attribution through case law illustrate the importance of a purposive approach to establishing corporate liability. Furthermore, the underlying relationship between the rules of attribution and the rules of agency indicate that the interests of risk-bearers and managers are not always aligned and should be redressed. Moreover, a realist approach as opposed to the fictional approach to attribution has been developed in English and Australian law. This approach focuses on the overarching corporate culture and identity when determining corporate fault, instead of individual corporate actors. These regulatory frameworks provide an alternative approach to the current South African model, which is based on the fiction theory. Lastly, the economic considerations, such as the separation of ownership and control and the agency problem, are evaluated to determine whether the current models of attribution create an economically efficient outcome or an unsustainable a risk-taking environment.
Keywords: Corporate culture; Corporate liability; Corporation law

Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch University, 2019)
Companies are legal persons and as much part of commercial traffic as the natural persons owning and controlling them. Compared to one another, companies and natural persons nevertheless have very different legal abilities and characteristics. It is therefore not unexpected that they are treated differently for purposes of the law of taxation. As a result it may often be more beneficial to have the profits generated by a business enterprise taxed in a company rather than in the hands of a natural person, especially in instances where a shareholder would be commercially indifferent to whether those profits are generated in a company or not. By using the separate legal personality of a company shareholders may often perpetrate an abuse of that separate legal personality. Such abuse of legal personality can also take place when legal personality is employed primarily for tax reasons. While a limited form of abuse of the corporate veil is tolerated, whether the use of separate legal personality for tax reasons amounts to an abuse thereof beyond what is permitted in South Africa can be determined in terms of three tests. These tests are the traditional “piercing of the corporate veil” judgments forming part of the common law, section 20(9) of the Companies Act 71 of 2008 and the General Anti-Avoidance Rules (“GAARs”) (and other specific provisions) in the Income Tax Act 58 of 1962. This dissertation considers when any of these various tests will dictate that the separate personality of a company be ignored (or “pierced”) for purposes of taxes levied in terms of the Income Tax Act. Through critical analysis of both the South African rules on piercing as applied for tax purposes as well as the circumstances under which selected other jurisdictions provide for piercing for tax reasons the dissertation formulates what best practice and desired policy for piercing for tax reasons are.
Keywords: Close Corporations Act, 1984; Companies Act, 2008; Corporate veil; Corporations; Income Tax Act, 1962; South Africa; Tax evasion; Taxation; Unconscionable abuse

Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch University, 2019)
ENGLISH ABSTRACT :This dissertation assesses the regulation of takeovers and mergers and the institutions created to enforce the law, from a comparative perspective. It uses South Africa as its point of departure and takes the laws of Delaware in the United States, the United Kingdom and Australia into account. The dissertation indicates that numerous takeover provisions in South Africa are poorly formulated, making them difficult to interpret and apply. Accordingly, the dissertation recommends amendment and improvement of certain Takeover Provisions. Special emphasis is placed on the mandatory offer requirement. The dissertation critically and comparatively analyses this requirement and especially its impacts on the market for corporate control, efficient usage of capital, corporate governance and (in South Africa) Broad Based Black Economic Empowerment. It appears from the literature explored that the mandatory offer requirement originated from the Perlman case in the United States as an expression of the equal opportunity rule. According to the equal opportunity rule, the controlling stake of a company is enriched with a premium of control, which must be shared with other shareholders when there is a change of the controlling shareholder. Shareholders must be given an equal opportunity to share in this control premium. Hence, a mandatory offer must be made to the remaining shareholders of the company by the new controlling shareholder at a price at which control was bought. Perlman case was decided in the United States of America during 1955. It is contended in the dissertation, that the mandatory offer requirement in section 123 of the Companies Act 71 of 2008 (“the Act”), can ultimately be traced back to this case. Researchers have criticised the mandatory offer requirement in a number of respects. It has been pointed out that the rationale for the decision in the Perlman case was not clear and applied in limited circumstances. Other scholars point out that the case was not a final decider on the sharing of the control premium due to later judicial pronouncements that differed with that case. Despite these commentaries, it appears that the case became a basis for imposing and enforcing this most debated rule in takeover and merger law. The dissertation concludes that the sharing of a premium of control, as envisaged by the mandatory offer requirement, is not enforced in the state of Delaware. It further concludes that in the UK, the mandatory offer rule forms the cornerstone of enforcement of the equal opportunity rule, but that widely dispersed shareholding ameliorates it negative consequences in that jurisdiction. The dissertation favours the Australian approach. That jurisdiction does not require a mandatory offer similar to that in section 123 of the Act, but, Australian Takeover Provisions, unlike their South African equivalent, have been tailor-made for Australian market conditions. The dissertation accordingly concludes that the mandatory offer requirement in section 123 of the Act in its current form is not appropriate for South Africa.
Keywords: Consolidation of corporations; Delaware; Great Britain; Merger of corporations; Regulation; South Africa

The definitions of ‘inside information’ and ‘insider’ in the Financial Markets Act 19 of 2012 - Van Der Walt, Johann Nico (Stellenbosch University, 2019)
The definitions of ‘insider’ and ‘inside information’ in the Financial Markets Act 19 of 2012 are, as is the case with their international counterparts, central to the Act’s regulation of insider trading. It has long been recognised, however, that those definitions, inherited from repealed companies and market abuse legislation, are cumbersome and counter-intuitive. This state of affairs obtains as the South African legislature has failed to undertake the most fundamental enquiry in formulating a coherent regulatory scheme aimed at prohibiting supposedly wrongful conduct: identifying a single theory of wrongfulness upon which to base its prohibitions. Instead, the definitions include elements of all possible regulatory bases for insider trading, including those having as their object the protection of proprietary rights in information and born out of the fiduciary doctrine. It is argued that the definitions, part of legislation aimed at addressing a financial market wrong, should be formulated with reference to the rights and obligations at play in those markets and the legislature’s objectives for those markets. A proposal is made in that regard.
Keywords: Finance; Financial Markets Act, 2012; Insider trading in securities; Markets; South Africa

The China-OHADA BIT, a step in the right direction : a new model of China-Africa BIT at a regional or sub-regional level - Sun, Sisi (Université de Montréal, 2019)
L’Afrique jouit non seulement de ressources naturelles, mais aussi d’un grand potentiel de marché. Ces dernières années, il y a une injection croissante d'investissements privés en provenance de Chine vers l’Afrique. La Chine souhaite exploiter le potentiel de l’Afrique en tant que marché émergent grâce aux investissements considérables réalisés par des entreprises privées. Parallèlement, les pays africains ont besoin d'investissements chinois dans divers domaines pour stimuler chaque aspect de leurs économies. L'investissement privé axé sur le marché nécessite un environnement d'investissement ouvert, stable, sécurisé et prévisible. Or, les traités bilatéraux d'investissement (TBI) existants entre la Chine et l'Afrique adoptent le modèle post-établissement axé sur la protection. La plupart de ces traités prévoient simplement des obligations générales de protection des investissements, laissant toutes les autres questions à la discrétion de l’État hôte. Les régimes juridiques instaurés par les TBI conclus entre la Chine et les États africains manquent de lisibilité, de prévisibilité et de cohérence. La conclusion de l'accord économique et commercial global entre l'UE et le Canada (AECG) suggère l’idée que la Chine pourrait s’inspirer de ce modèle pour conclure un accord bilatéral autonome avec les pays africains au niveau régional ou sous régional afin d’attirer des investissements chinois vers l’Afrique. Cet accord pourrait intervenir dans le cadre de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) étant donné son niveau d’intégration et son autorité en matière de commerce et d’investissement sur le continent. Ce TBI modèle comportera des normes uniformes en matière d’accès aux marchés et de protection des investissements, ce qui limitera les risques d’interprétation divergente et partant, contribuera à l’instauration d’un climat d'investissement stable, sûr, prévisible et plus ouvert. Africa enjoys not only natural resources, but also market potential. There has been a growing injection of private investment inflows from China to Africa recently. China needs to exploit Africa’s potential as an emerging market for its tremendous investments by private enterprises. Moreover, the African countries need Chinese investments in various areas to boost aspects of their economies. Private, market-oriented investment calls for an open, stable, secure and predicable investment environment. However, existing bilateral investment treaties (BIT) between China and Africa adopt the protection-oriented, post-establishment model. The treaties merely provide for some general obligations of investment protection, leaving all other matters to the policy discretion of the host state. The China-Africa BIT regime is sporadic, uninformed and incoherent. The conclusion of the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA) develops the idea that China might conclude a standalone BIT with the African countries at a regional or sub-regional level to attract Chinese investment inflows into Africa through an open, coherent and uniformed investment scheme. Given the integration of Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) to be one single jurisdiction over trade and investment, the China-OHADA BIT is the one most likely to be expected. This standalone BIT regime inherently calls for an absolute standard for market access and investment protection, and uniformity to limit the discretion of interpretation, and as such, contribute to a more open, stable, secure and predictable investment climate.
Keywords: BIT regime; China-OHADA BIT; Chine-OHADA TBI; Climat d'investissement; Discrétion politique; Investment climate; Investments; Policy discretion; TBI modèle

The Development of Mortgage Finance in Nigeria and its Impact on the Economy - Siyan, Peter; Adegoriola, Adewale E; Erivwode, Ovosa Mercy (International Multilingual Journal of Science and Technology, 2019)
This study examines the development of mortgage finance in Nigeria and its impact on economic growth. Aggregate housing finance data for by both banks and non-financial institutions was used to measure housing finance. Other variables considered include financial debt proxy by M2Per capita, financial instability proxy Interest rate and the level of development of the capital market measured by market capitalization. Time series data covering the period 1990-2016 was obtained from Central Bank statistical bulletin, National Bureau of Statistic and World Bank. The methodology adopted in the study is Vector Autoregressive Model (VAR) was estimated using linear regression method. The results of the analysis indicated that there is a one-way causal link runs from mortgage finance to economic growth. In addition, mortgage finance was found to be a significant determinant of increasing pattern of economic growth over a long period of time. Due to the level of the country’s financial depth, it was recommended that Nigerian government should intensify effort aimed at consolidating the level of financial re-structuring in the non-financial sector which mortgage financing belong. The central bank should make a policy stipulating commercial banks to set aside certain proportion of their total assets to finance housing demands.
Keywords: Economic growth; Hypothèque; Mortgage Finance; Vector Autoregressive

Proceedings ISDS reform conference 2019: mapping the way forward - Asian Academy of International Law (2019)
Keywords: Dispute settlement; Investment disputes; LAW REFORM; UN Commission on International Trade Law

The copyright protection of musical works : a historical and contextual analysis - Baloyi, Jele Joel (University of South Africa, 2019)
This work is concerned with an analysis of the copyright protection of musical works. Musical works form part of the categories of works protected under copyright law. It would be easy to dismiss musical works as not warranting a serious study, as would for example, be warranted for “industrial property” rights such as patents and geographical indicators, or more “serious” copyrights such as architectural works and computer software. Such a perspective would however, not be cognisant of the significant contribution that the music industry, as part of the broader cultural and creative industries makes to the global economy. It has, for example, been shown that in 2013, the global cultural and creative industries contributed some US$2,250b, employing some 29,5 million people, with the music industry being one of the top three employers and with its revenues exceeding those of radio.1 A single successful musician can earn in excess of US$100m per annum,2 making the industry ripe for litigious claims. For this reason therefore a consideration of the legal rules that apply to the protection of musical works is crucial. There is currently no clear exposition and systematic analysis of the legal principles applicable to the field of music copyright and no work devoted to the in-depth delineation of the rights and sub-rights relating to musical copyright protection. This study seeks to address this research and knowledge gap by providing a historical and contextual analysis of the protection of musical works. The aim is to provide a complete picture of the milieu of music copyright protection to enable the reader to feel empowered in dealing with the subject-matter. This the writer does by mapping the historical development of music copyright protection in particular from eighteenth century England when the first copyright legislation was enacted, until the enactment of the British Copyright Act of 1911, which signalled the emergence of the “common law” copyright system. The writer then shows how this enactment shaped the development of modern music copyright law, and concludes by presenting a contextual consideration of the current South African law of music copyright and highlighting the challenges it is faced with.
Keywords: Copyright; Copyright protection; Dramatico-musical works; Imperial Copyright Act; Intellectual property; Intellectual property rights; Music; Music trade; Musical compositions; Musical works

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Shareholder activism, corporate social responsibility and financial performance - Yang, Yi (Victoria University of Wellington, 2019)
The thesis examines the influence of shareholder activism on corporate social responsibility (CSR) disclosure of targeted firms and its spillover effects on CSR disclosure, corporate social performance (CSP) and financial performance (FP) respectively in peer firms. The research is motivated by filling the research gaps in prior literature and providing insights to shareholders, the management and regulatory bodies in practice. The thesis consists of three parts. Firstly, this thesis reviews the literature surrounding shareholder activism by conducting narrative reviews of 92 working papers and publications and meta-analysis on 55 working papers and publications, published during 2000-2017 period. Theories from prior literature, namely agency theory, stakeholder theory and stakeholder salience theory are analysed through narrative review analysis at the beginning of the chapter. Then, the analysis of narrative review also documents mixed findings of the associations among shareholder activism and FP and CG and CSP, including spillover effects. That is, the associations could be positive, negative and not significant in prior literature. The results of meta-analysis indicate that shareholder activism improves FP and CSP respectively. In addition, the thesis also examines the major types of shareholder activists and main forms of shareholder activism. Overall, through the analysis, the thesis identifies the research gaps of prior literature, thereby pointing out future research directions. Secondly, by employing shareholder proposals from Standard & Poor's 1,500 (S&P 1,500, hereafter) companies in the United States as a proxy of shareholder activism during 2006-2014 period with 13,572 separate observations, this thesis examines whether the whole sample of shareholder activism, institutional shareholder activism and coordinated shareholder activism could influence CSR disclosure level respectively. Simultaneously, this thesis also investigates whether shareholder activism affects CSR disclosure level given the other corporate governance mechanisms, namely board size, the presence of female directors, outside directors and CEO incentives. The results typically demonstrate that: (1) while shareholder activism negatively relates to CSR disclosure level, larger board size or the presence of female directors combined with shareholder activism directly relates to maintaining better CSR transparency; (2) coordinated shareholder activism could decrease social disclosure level. The findings also indicate that CSR disclosure provides an approach to strategically manage risks. Thirdly, the thesis explores spillover effects from different types of shareholder activism on CSR disclosure level, CSP and financial performance by using data gathered from S&P 1,500 companies during 2007-2014 period. The findings show that shareholder activism increases social disclosure level and environmental disclosure level in peer firms. It also shows that there is a weak positive association between shareholder activism and CSP. It therefore demonstrates the weak influences of shareholder activism in changing firms’ CSP. It also illustrates that institutional shareholder activism has an advantage over coordinated shareholder activism in terms of increasing corporate transparency. In this manner, it indicates that the collective action problem among coordinated shareholders could also attenuate the impact of shareholder activism in peer firms. The thesis contributes to the literature on shareholder activism practically and theoretically. The findings provide useful insights to shareholders, management teams and regulatory bodies for their policy-making. Beyond the practical contribution, the thesis also provides empirical evidence to stakeholder salience theory and analyses the collective action problem.
Keywords: CSR disclosure; Corporate Social Responsibility; Corporate governance; Corporate social performance; Financial performance; Shareholder activism

Choice of law in International Commercial contracts in the BRICS countries - Agbeko, Fafa Delight (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The tax trade interface : an investigation of the influence of the Nigerian income tax incentives on taxpayer behaviour - Aniyie, Ifeanyichukwu Azuka (University of Pretoria, 2019)
The Companies Income Tax Act provides the architecture for corporate income taxation (CIT) in Nigeria. It specifies the rate, the tax base and contains the bulk of the incentives to which qualified corporate taxpayers are entitled. This thesis investigates the influence of incentives on the compliance behaviour of micro and small companies (MSCs) in Nigeria. By Nigeria’s standard, these are companies which: (1) employ between 1 to 49 persons and/or own assets (excluding land and building) valued at less than NGN 100million; or (2) are either private limited companies or one-man businesses. In the context of the Nigerian tax system, MSCs are corporate taxpayers with turnover of less than NGN 200 million. This choice of research population is a consequence of the globally acknowledged niche occupied by MSCs vis-à-vis the of the socio-economic objectives of any state. In the course of the study, the formulated research questions were resolved using a multi-stage mixed methods framework which allowed for the fusion of qualitative and quantitative epistemology as well as facilitated the introduction of pragmaticism into the research process. The thesis, inter alia, identified gaps in the administrative regime of CIT incentives in Nigeria and highlighted the fact that they have the potential to introduce uncertainty into the tax system. In addition, it revealed that the regulatory regime for the role and services of tax intermediaries within the tax system, in terms of current standards and reality, is sub-optimal. On the basis of a survey of a small sample of MSCs, it was concluded that the influence of tax intermediaries with regard to the compliance behaviour of MSCs was marginal. Reason for this was traced to the fact that the role and services of the latter vis-à-vis clients who are MSCs are actuated by variables which are within the psycho-social space of the tax intermediairies and the desires/requests of the MSC. This dismisses, in the context of Nigeria, the notion that the tax intermediary is the initator of every tax dodge. Based on the findings, the thesis, inter alia, recommended a re-orientation in the conceptualisation of tax compliance as the prevailing theoretical premise for the extant tax law and policy does not contemplate that non-economic factors and referents outside the realm of taxation are capable of influencing tax compliance behaviour. In addition, recommendations with the capacity to change the law, policy and administrative regime relating to CIT incentives as well as the role and services provided by tax intermediaries were made after an examination of the situation in Kenya and South Africa.
Keywords: Companies Income Tax Act; Corporate income taxation; Income tax; Nigeria; Tax trade; Taxpayer

Rethinking international employment contracts in the wake of the Fourth Industrial Revolution - Antwi-Larbi, Nana Amobea (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Choice of forum in International Commercial Contracts : a comparison of the position in Ghana and under the Brussels IBIS regulation - Asante-Aboagye, Benedicta (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Belgium; Border trade; Conflict of laws; Ghana; International commercial contracts; Litigation

May an employer dismiss an employee if the disciplinary chair imposed a lesser sanction? South African Revenue Service v Commission for Conciliation Mediation and Arbitration 2017 38 ILJ 97 (CC) - Calitz, Karin Beatrix (Stellenbosch Law Review, 2019)
In South African Revenue Services v Commission for Conciliation, Mediation & Arbitration, Kruger, the employee, called his superior a “kaffir” on more than one occasion. The employer unilaterally dismissed the employee after the chairperson of the disciplinary hearing had imposed a lesser sanction. In doing so, the employer disregarded the collective agreement which did not make provision for the sanction of the disciplinary chair to be substituted. The employee claimed that his dismissal was invalid and therefore unfair. The Commission for Conciliation Mediation and Arbitration (“CCMA”), Labour Court and Labour Appeal Court (“LAC”) agreed. However, in the Constitutional Court (“CC”) the employer no longer argued that it was entitled to substitute the sanction in the light of the breach in the trust relationship, but only alleged that reinstatement was a remedy that no reasonable decision-maker would order. The CC agreed and held that the dismissal was substantively fair but procedurally unfair. The CC did not answer questions of lawfulness, fairness and invalidity, but in Steenkamp v Edcon the CC held that employees claiming remedies for unfair dismissal in terms of the Labour Relations Act 66 of 1995 (“LRA”) should not rely on invalidity. However, employees still have the right to common-law remedies based on their employment contract. Considering the importance of collective agreements, negotiated disciplinary codes, certainty and consistency, and to avoid employers exercising unfettered power over employees, state organs should apply for a review of an unsatisfactory sanction by the disciplinary chairperson in terms of section 158(1)(h) of the LRA. Private employers could negotiate a disciplinary code which allows both the employer and employee to appeal against the decision of the disciplinary chair which should make provision that a more severe sanction can be imposed on appeal.
Keywords: Arbitrage; Arbitragem; Arbitration; Commission for Conciliation; Dismissal of employees; Labor discipline; MARD; Mediación; Mediation; Mediação; Médiation; South Africa; South African Revenue Services

The treatment and recognition of company groups in South African corporate law - Diale-Ali, Regomoditswe Ursula (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

A critical appraisal of call centre contracts for insurance - Dladla, Mbongeni George (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Copyright as a constraint on creating technological value - Drążewski, Kasper (European University Institute, 2019)
How do we legislate for the unknown? This work tackles the question from the perspective of copyright, analysing the judicial practice emerging from case law on new uses of intellectual property resulting from technological change. Starting off by comparing results of actual innovation-related cases decided in jurisdictions with and without the fair use defence available, it delves deeper into the pathways of judicial reasoning and doctrinal debate arising in the two copyright realities, describing the dark sides of legal flexibility, the attempts to ‘bring order into chaos’ on one side and, on the other, the effort of judges actively looking for ways not to close the door on valuable innovation where inflexible legislation was about to become an impassable choke point. The analysis then moves away from the high-budget, large-scale innovation projects financed by the giants of the Internet era. Instead, building upon the findings of Yochai Benkler on the subject of networked creativity, it brings forth a type of innovation that brings together networked individuals, sharing and building upon each other’s results instead of competing, while often working for non-economic motivations. It is seemingly the same type of innovation, deeply rooted in the so-called ‘nerd culture’, that powered the early years of the 20th century digital revolution. As this culture was put on trial when Oracle famously sued Google for reuse of Java in the Android mobile operating system, the commentary emerging from the surrounding debate allowed to draw more general conclusions about what powers the digital evolution in a networked environment. Lastly, analysing the current trends in European cases, the analysis concludes by offering a rationale as to why a transformative use exception would allow courts to openly engage in the types of reasoning that seem to have become a necessity in cases on the fringes of copyright.
Keywords: Copyright; Fair use (Copyright); Intellectual property

COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element (Publications of the Masaryk University, theoretical series, editions Scientia, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna

The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

The challenge of three-dimensional printing : questioning established concepts in intellectual property law - Elam, Viola (European University Institute, 2019)
Over the last years, academics, practitioners and policy makers have focused their attention on an emerging technology: three-dimensional printing (“3DP”). 3DP is often portrayed as a game changer, showing the potential to disrupt established socioeconomic paradigms and exert profound implications in disparate areas of law. 3DP not only is well integrated in the manufacturing industry, but also increasingly adopted at consumer level. Recent developments have made it possible for ordinary people to take an active role in the production, customization and distribution of goods, and likewise paved the way for the proliferation of new market entrants, such as 3DP online platforms. Against this background, this thesis aims to shed some light on the implications that 3DP may have for Intellectual Property Law. In particular, this work attempts to predict and grasp the consequences that the digitization of real world things may carry in the area of IP law, both from the side of protection and infringement. This contribution is intended to create general awareness about the current state of the art and likewise delineate possible future scenarios in the 3DP ecosystem. The research question at the core of the analysis is whether the current legal framework of different IPRs already offers suitable means for regulating the thin dividing line between the digital and the analogue world, or rather needs to be amended, in order to cope with such a fascinating reality. To this end, the analysis contributes insights to the best legal treatment that CAD files shall receive, in case such files embed products protected by copyright, designs, patents and trademarks. Hence, it addresses right owners’ concern that the online transmission of CAD files, combined with the ease of converting such files into the final printout, will facilitate mass-scale and worldwide infringement of all IPRs.
Keywords: 3D; Copyright; Intellectual property; Three-dimensional printing

A Critical Look at the Mechanism for Challenge of Arbitrators Under ICSID Convention and Arbitration Rules - Gautama, Ivan (Juris Gentium Law Review, 2019)
Administered arbitrations under ICSID are amongst the most-utilized means to resolve investor-state disputes. Part of why it is so is because the ICSID as an institution is heavily affiliated with the World Bank. This affiliation serves as a double-edged sword in ICSID’s hands: while on one side such affiliation lends ICSID the credibility any successful arbitral institutions need, on the other side ties between the two institutions are proving to become too close for comfort. This paper explores what could go and has gone wrong in the past within the current ICSID arbitration system with regards to the mechanism for challenging arbitrator(s), and whether such mechanism allows ICSID to effectively deliver what it is expected to provide.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Conflict of interest; ICSID; Investor-State; World Bank

The role of the Hague principles on choice of law in international commercial contracts in Japanese private international law - Geraghty, Brandon Brian (University of Johannesburg, 2019)
Please refer to full text to view abstract LL.M. (International Commercial Law)
Keywords: Conflict of laws; Contracts (International law); Japan

A comparative analysis of mergers and acquisitions in South Africa, Botswana and Kenya : how can we achieve successful integration in Africa? - Gumede, Nomfundo Pretty (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Acquisitions; Amalgamation; Bots; Business; Corporate mergers; Integration; Kenya; Mergers; South Africa

Voluntary membership: up to which point do cooperatives support liberalism? - Hiez, David (International Journal of Cooperative Law, 2019)

Women in private international law - Keyes, Mary E. (Research Handbook on Feminist Engagement with International Law, 2019)
There has been almost no consideration of the position of women in private international law. There is very little published research applying a feminist analysis to, or even considering the position of women in, private international law. This field gives almost no attention to the particular interests, positions and experiences of women as subjects of the law, or the contribution of women as makers of the law. In the common law, private international law was largely developed in the 19th century, by male judges who were strongly influenced by commentary written exclusively by men. This chapter establishes that the apparently gender-neutral nature of private international law conceals profoundly ingrained assumptions about gender, in which the masculine is represented as a rational and sophisticated businessman, and the feminine is represented as a legally incapable wife. It then considers the gendered dimension of private international law in international family law, referring in particular to the regulation of international child abduction, international family property agreements, and international commercial surrogacy. Each of these examples demonstrates the differential impact of the law on women, indicating the need for greater awareness of and attention to gender. It concludes that while there have been some advances recently, particularly in terms of increased representation of women in making and commenting on private international law, there remains a great need for further research into the position of women as legal subjects and law-makers in this field.
Keywords: Private International Law; Woman

Expanding access to justice: an exploration of large firm pro bono practice across Europe - Khadar, Lamin (European University Institute, 2019)
This PhD thesis explores pro bono practice among large, international law firms in Europe. The central question addressed by the thesis is: does “Big Law Pro Bono” contribute to access to justice in Europe? The thesis commences with a review of the literature which both contextualizes and situates the thesis. This review also identifies gaps in the existing literature particularly related to the globalization and localization of law firm pro bono and its practice beyond the United States (i.e. its practice in other parts of the world such as Europe, Asia, Africa and Latin America). After identifying issues with the current definition of access to justice, used throughout much of the existing literature, the thesis proposes a new definition which is then used throughout the thesis to evaluate pro bono practice in Europe. Towards this end, the thesis first provides historical context to law firm pro bono practice by exploring the history of pro bono, legal aid and other models of progressive lawyering across Europe. Following this, the thesis closely explores the process by which large firm pro bono practice arrived in Europe (i.e. globalization), the contemporary practice and the process by which it adapted to the European legal, social and political ecosystem (i.e. localization). Ultimately, it is suggested that large firm pro bono does not contribute to access to justice in Europe insofar as access to justice is defined narrowly - in the way that it has been conceived of in much of the existing literature. However, by embracing a broader definition of access to justice, it is possible to perceive the actual (and possible) social and political impact of large firm pro bono practice in Europe.
Keywords: Justice; Legal assistance to the poor; Legal services

The contractual landscape and the protection of consumers in online auction contracts - Khan, Haleema (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Aquilian liability : the best remedy against delinquent company directors - Kharametsane, Godirilwe (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations

Online Dispute Resolution: Methods and Effects - Kumari, Poonam; Sood, Geetika (International Journal of Science and Research, 2019)
The concept of online dispute resolution came with the development of e-commerce. It is a branch which resolves the dispute between parties without interference of court. It includes arbitration mediation and negotiation. It also includes consumer to consumer disputes. With the emerging to globalisation the concept of online dispute resolution emerging day by day. The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. Thearticle is a study of ODR, online mediation and electronic arbitration. It includes their uses and their relationships with e-commerce. The paper is regarding primary aspects of online dispute resolution, its definition and its growth and development. It also includes the relationship between ODR and technology. Research paper isdiscussing the two forms of ODR: online mediation and electronic arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Online Dispute Resolution

Rationality and legality of non-market economy treatment in Antidumping law: novel perspectives on the changed legal environment - Long, Shao (Universität Wien, 2019)
AD Recht ermöglicht die Anwendung des Instruments nichtmarktwirtschaftlicher Behandlung (NME) zwecks Bestimmung des normalen Ausfuhrpreises von importierten Waren aus Ländern deren Märkte als weitgehen von Regierungen beeinflusst und deren Preise und Kosten für diese Berechnung als unverlässlich angesehen werden. Stattdessen sollten diese Berechnungen auf der Basis von Preisen in einem Vergleichsland mit funktionierender Marktwirtschaft ( „surrogate country‟ ) erfolgen. Die vorliegende Dissertation legt dar, dass die Anwendung der NME Behandlung zum Schutz gegen unfairen Importwettbewerb nicht auf rechtlich gesicherter Grundlage erfolgt, sondern als willkürlich eingeseztes protektionistisches Instrument gehandhabt wird. Besonders die Anwendung dieser Methode auf Chinesische Exporte nach 2016 ist rechtlich fragwürdig. Die Dissertation untersucht die Rechtmäßigkeit und Zweckmäßigkeit diese Methode, erstens durch die Analyse der wirtschaftlichen Begründung des AD Rechts und der geschichtlichen Entwicklung seit seinen protektionistisch motivierten Anfängen. Sie untersucht sowohl die relevanten Regeln und Praktiken aus der Zeit vor der Gründung der WTO als auch solche die danach zur Anwendung kamen und kommt zum Schluss, dass sie angesichts des grundlegend geänderten globalen rechtlichen Umfelds nicht mehr tragbar sind. Die Autorin empfiehlt daher, dass die auf NME Behandlung bezogenen Regeln und Praktiken vollständig aufgegeben werden und im Rahmen der gegenwärtigen Bemühungen um eine Modernisierung des gesamten WTO Regelwerks durch angemessene andere Regeln ersetzt werden sollten.
Keywords: Antidumpingrecht; Nichtmarktwirtschaftlichen Behandlung; Non-market economy

An analysis of reinstatement as a primary remedy for unfair dismissal of employees in South African Labour Law - Mampholo, Yvonne Mokhubane (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Intermediaries and advisors' duties to disclose onerous clauses to prospective policyholders - Matshitse, Collen Kgaolo Stephen (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Commercial law; Insurance law

The recovery of cultural property in international law: collaborative settlements of disputes - Mauro, Benedetta (LUISS Guido Carli, 2019)

Curbing transfer pricing manipulation in South Africa : lessons from selected jurisdictions - Mboweni, Abel Mabawuzeni (University of Pretoria, 2019)
Transfer pricing manipulation is a worldwide problem which results in a massive loss of revenue which is meant to finance government socio-economic programmes. South Africa is not immune to this problem. South Africa is losing billions of Rands in tax revenue due to this scourge. This research is an attempt to find ways and means which can be employed to combat or control the problem. In order to find the envisaged solutions, this research investigates the causes of the problem by analysing the weaknesses and the strong points of the arm’s length principle which is the basis of transfer pricing practice in South Africa and elsewhere. The research also investigates and analyses the corporate reasons for Multinational Enterprises (MNEs) to engage in transfer pricing with a view to demonstrating that transfer pricing is a neutral tax avoidance concept if it is applied for genuine business considerations. The investigation also entails analysing the legal framework of transfer pricing in South Africa which is embodied in section 31 of the Income Tax Act 58 of 1962. The research analyses the efficacy of section 31 in dealing with the sophisticated transfer pricing manipulation schemes. In addition, an extensive reference to the Organisation for Economic Co-operation and Development (OECD) Transfer Pricing Guidelines is made as South Africa relies heavily on the guidelines. A comparative analysis of selected topics is also conducted with the United States (US) and India with a view to drawing lessons from those jurisdictions. Based on the outcome of the analysis and the lessons drawn from the comparative analysis, findings are presented followed by legislative proposals or recommendations which will help to eradicate the problem. It is hoped that implementation of the recommendations taking into account the socio-economic conditions of South Africa will help to deal with the problem.
Keywords: Loss of revenue; South Africa; Tax Revenue; Transfert pricing

An investigation into the effectiveness of trade unions in advancing the cause of workers during strikes in the face of an emerging culture of violence and criminality - Mfusi, Pearl Dawn Arnold (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Labour protests; Liability; Strikes; Trade unions; Violent protests; Violent strikes; Workers

Towards development-centred trade relations: a study of South Africa and the USA trade relations with particular focus on the African Growth and Opportunity Act (AGOA) - Mkhwanazi, Nhlakanipho (University of KwaZulu-Natal, 2019)
With trade taking place continuously on a daily basis, its often-reported success gives the impression that all participants involved are to a certain extent somewhat successful too. This dissertation draws attention to the discrepancies that have often gone unnoticed throughout the decades and the effects that have arisen as a result. South Africa’s (SA) and the United States of America’s (US) trade relationship through the African Growth and Opportunity Act (AGOA) is the focus of this study, with this relationship being analysed from as far back as history has been recorded to the modern day. Least developed countries (LDCs) are an integral part of this study because most trade-related activities involve them, and they contain most of the world’s natural resources, but most importantly they also make up a large portion of the world’s population. It's baffling to see that where these factors are present, there's also inequality. Seemingly, there are efforts that deal specifically with the challenges faced by developing countries, but what is concerning is these solutions are formulated by developed countries which created them and continue to perpetuate them. The approach adopted was mostly that of contrasting events that have involved trade over the decades and a discussion of how these events have shaped international, political and trade relations, that is, the existing status quo. Examples include the two World Wars; oppressive regimes such as apartheid; and the formation of global institutions ranging from the International Trade Organization (ITO) to the General Agreement on Tariffs and Trade (GATT), and the World Trade Organization (WTO). The first three chapters contain an introduction, a background focus on development and the history of relations between South Africa and the United States of America. The last two chapters contain a discussion on AGOA as well as findings and recommendations that can be implemented to assist with this issue. What this dissertation was aiming to establish was the perpetual involvement of developed countries in the affairs of developing countries. This is illustrated through the renegotiation of the AGOA in 2015, where SA had to accept ultimatums set for it by the US. This dissertation further shows that such tactics are nothing new when the US is involved, as is evidenced by its involvement in major global events that have shaped the course of history. This approach is not only harmful but also stagnates development, as developing countries must adhere to agreements that sometimes are not to their benefit. The findings indicate a contradictory pattern: when solutions to challenges faced by developing countries are presented, they translate instead into a further stronghold over developing countries because of past atrocities such as colonisation and apartheid. What appears throughout the dissertation are the ever-present structures that are intended to perform functions supposed to be for the improved good of developing countries, but which result in those countries facing never-ending challenges, some of which are self-inflicted through alliances such as the AGOA with developed countries.
Keywords: AGOA; African Growth and Opportunity Act; Developing countries; Dumping; GATT; General Agreement on Tariffs and Trade; Trade relations; WTO; World Trade Organization

Sustainable tourism development in transfrontier conservation areas : a legal perspective - Mugadza, Amanda Tapiwa (North-West University, 2019)
Transfrontier conservation areas (TFCAs) originate from the idea of conservation across international boundaries. Within the SADC region, they are defined as areas or components of large ecological regions that straddle the boundaries of two or more countries, encompassing one or more protected areas, as well as multiple resource use areas. While the objectives of TFCAs are manifold, key among these are biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development. Within SADC, tourism is identified as a key driver of these objectives. To explore this further, the study embarks on a case study of the Great Limpopo Transfrontier Conservation Area (GLTFCA), the oldest and second largest TFCA in the region, involving South Africa, Mozambique and Zimbabwe. From the GLTFCA, it is established that challenges exist with the manner in which tourism development is undertaken. However, it is further established that these challenges do not necessarily stem from the tourism development itself but from the weaknesses in the governance structures of this TFCA. In particular, the exclusion of local communities as key governance actors in the GLTFCA is seen to be detrimental to conservation and perpetuates poverty. Superimposed on these weaknesses, the tourism development therefore fails to adequately promote biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development in the GLTFCA. To resolve these challenges, the study explores the concept of sustainable tourism development from a legal perspective guided by the question: what is the legal framework necessary, at domestic level – in TFCA participating countries to ensure that sustainable tourism development promotes the key SADC TFCA objectives? Through the aims or policy implications of sustainable tourism development, the study determines a legal framework comprising of the relevant TFCA governance actors as well as the governance-based tools that are necessary to promote the TFCA objectives. The domestic legal frameworks of the GLTFCA participating countries are measured against this legal framework to establish whether they promote sustainable toruism development. It is established that the domestic legal frameworks of South Africa, Mozambique and Zimbabwe, individually and as a whole, neither provide effectively for all relevant TFCA governance actors, especially local communities; nor for the tools that promote biodiversity conservation, the improvement of livelihoods-alleviation of poverty and economic development in the GLTFCA. Thus, the legal framework of the GLTFCA does not provide for sustainable tourism development as it should. For this reason, the study’s principal recommendation is the adoption, by all SADC TFCA participating countries, of a domestic legal framework for sustainable tourism development with specific elements which provides for the key TFCA governance actors as well as the relevant governance-based tools.
Keywords: Biodiversity conservation; Domestic legal framework; Economic Development; GLTFCA; Governance actors; Governance-based tools; Improvement of livelihoods; Sustainable tourism development; TFCAs; Tourism

Price reduction as a remedy for breach of contract by the seller under the CISG and English law - Mukuna, Nomator (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Interrogation proceedings in insolvency law: a comparative study - Mwelase, Musamuni Barrah (North-West University, 2019)
Interrogation proceedings in insolvency circumstances have always been a thorny issue in South Africa, even prior to the advent of the new constitutional democracy. After the adoption of the new Constitution in 1993, a number of court cases seeking adjudication on constitutional compliance came before our courts. The insolvency of both natural and juristic persons necessitates the employment of specified proceedings such as insolvency interrogations. The latter is done to enable an efficient and effective collection and collation of information that would assist in the administration, sequestration and winding-up of the affairs of the affected person. These proceedings are intended to benefit creditors of an insolvent (natural and juristic). The matters of Ferreira v Levin; Vryenhoek v Powell 1996 (1) SA 984 (CC) (1996) (1); Bernstein and Others v Bester 1996 (2) SA 751 (CC); Harksen v Lane 1998 (1) SA 300 (CC; De Lange v Smuts 1998 (1) SA 736 (C) are still leading cases in relation to the constitutionality of interrogations in insolvency circumstances. The Constitutional Court has on a number of occasions, declared the interrogation proceedings in insolvency matters constitutional, with minor amendments on a case-by-case basis. The effect of these judgements is that, in every case in which an insolvent debtor has to undergo an interrogation process, the presiding officer must ensure that compliance with the constitutional requirements are in place. The current position in which the sequestration of insolvent estates and the winding-up of insolvent companies are respectively regulated by two statutes, is a matter for concern. This situation has led to duplication and contradictions in the two statutes. Further, the absence of specialist tribunals or officers dedicated to the administration of insolvency related matters is a further hurdle to the effective and efficient finalisation of the affairs of insolvent estates or insolvent companies’ affairs. The matter of Leong comes to mind. In this case, the Master of the High Court issued a warrant of arrest for a witness who was subpoenaed to appear at the meeting of creditors in his insolvent estate. This was the case, despite the fact that Leong had previously submitted a medical certificate to the effect that he was unable to attend the meeting due to illness. This case is a clear indication of a lack of proper guidelines to deal with insolvency related matters - for non-judicial officers (such as the Master of the High Court). This incident took place in 2016, long after the decision in De Lange v Smuts 1998 (1) SA 736 (CC). Interrogation processes in insolvency circumstances in Namibia and Botswana are almost similar to South Africa’s processes. Divergent provisions in Namibia and Botswana exist, but not to a great extent. Like South Africa, the above-mentioned jurisdictions adopted a constitutional democracy long before South Africa. One would have expected that interrogation proceedings in insolvency circumstances would be in line with human rights. Further, as is the case in South Africa, insolvency of natural persons and of juristic persons are regulated by two separate statutes in these jurisdictions. This thesis investigates issues relating to the interrogation process in insolvency proceedings in the three SADC countries, namely South Africa, Namibia and Botswana. It compares the position to two foreign jurisdictions, namely England and Canada – as leading jurisdictions in human rights. Thereafter, suggestions on processes and methods of information gathering in line with human rights and in specialist tribunals will be made. In addition, recommendations for inclusion in a unified statute regulating insolvencies of both natural and juristic persons will be made. This will be done taking into consideration the economical and socio-political circumstances of South Africa and the SADC countries forming part of this thesis.
Keywords: Insolvency; Private enquiries; Public enquiries; Subpoena; Summons; UNCITRAL Model Law; World Bank

An appraisal of the provision of "benefits" as an unfair labour practice in South African labour law - Newaj, Kamalesh (University of Pretoria, 2019)
This thesis seeks to resolve the ambiguities surrounding the use of the unfair labour practice relating to the provision of “benefits” as a dispute resolution mechanism in South African labour law. This mechanism has been plagued with uncertainty, primar-ily because of the lack of a statutory definition of benefits. Evidently, the interpretation and application of benefits have been left to the courts, resulting in two diverse ap-proaches being endorsed. The first one sought to confer a narrow connotation on ben-efits, the rationale being to separate benefits from the definition of “remuneration”. It further sought to limit the use of this unfair labour practice to instances where the benefit claimed was exclusively provided for ex contractu or ex lege. The primary ob-jective was to protect the divide between disputes of right and disputes of interest, a distinction that is recognised and encouraged in our law. The second approach was one that fostered an expansive interpretation of the term, deeming it to be part of re-muneration. Needless to say it resulted in countless items being subject to determina-tion as benefit disputes. Furthermore, it extended benefits beyond those rooted in con-tract or legislation, including those granted or offered subject to the exercise of mana-gerial discretion. The supplementary challenges firstly relate to the absence of statutory direction on the standards of fairness to be applied in evaluating employer conduct. Secondly, the judiciary has provided opportunities for employees to utilise recourse other than the unfair labour practice provisions to address benefit disputes. Such leeway comes in the form of contractual recourse as well as the ability to institute strike action. In search of solutions to the problems identified above, the study explores and anal-yses the history of the unfair labour practice concept. Thereafter, an extensive exam-ination of the developments in this area of the law is undertaken. This includes a com-prehensive analysis of legislation, case law and academic writings. Having docu-mented and analysed the South African position both pre- and post-democracy, the study critically evaluates these sources of law. The study further involves a diagnostic assessment of international legal instruments and foreign law in order to extract best practices. The conclusions reached are, firstly, that an expansive interpretation of benefits is warranted. This is in line with a purposive interpretation of the LRA, which promotes the constitutional right to fair labour practices and international law. This study there-fore proposes a wide-ranging definition of the term benefits. Secondly, standards of substantive and procedural fairness have been found to be applicable in evaluating employer conduct. As such, fairness guidelines based on these standards have been developed. Thirdly, in respect of the alternate avenues available to resolve benefit disputes, it has been found that although there are strong indicators that point to a conclusion that contractual recourse has been supplanted by statutory recourse, such a finding cannot be definitively made. Furthermore, section 64(4) as it stands provides for the right to strike over unilateral changes to terms and conditions of employment, which includes unilateral changes to pre-existing benefits. However, the judiciary can limit the use of this section in benefit disputes by prioritising the substance of the dis-pute over its form. This thesis ultimately proposes the incorporation of a Code of Good Practice into the LRA. The Code of Good Practice: Benefits adopts the principal research findings of this study. It encourages the enforcement of benefit disputes through the dispute res-olution institutions set up by the LRA. The adoption of this Code (The Code of Good Practice: Benefits) will bring certitude to this field of labour law.
Keywords: Labour law; Labour practice; South Africa

The interruption of liquidation by business rescue application: a lacuna in the Companies Act - Ntingane, Neo Samantha (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The rights of illegal workers not to be unfairly dismissed, with emphasis on illegal immigrants and sex workers - Ntshalintshali, Phindile Ziningi Glenn (University of KwaZulu-Natal, 2019)
Illegal workers have been and continue to be the most vulnerable category of employees in the labour market, the reason for this is the invalidity of their employment contract due to illegality. For the longest time, the Labour Relations Act (hereinafter the LRA) has not been able to afford these workers protection because they did not fall within the ambit of the legal definition of ‘employee’ and the Act only recognises employees as holders of the rights provided for under the LRA. As a result of the Act not being able to protect these workers, they have become victims of exploitation and vicious abuse in the hands of their employers, making them vulnerable in their employment relationship. The law concerning illegal workers has since changed. Courts have found that these workers are in fact employees for the purposes of the LRA, and that, for an employment relationship to exist there need not be a valid employment contract in existence. An employment relationship may take various forms and the goal that the Labour Relations Act seeks to achieve is to protect those employees who find themselves vulnerable as a result of the illegality of their employment contract. It has also been argued that the law aims mostly at penalising the employer rather than the employee who is economically and socially weaker than the employer, therefore, courts have found that the Labour Relations Act should be interpreted in a manner that is consistent with the Constitution of the Republic of South Africa (hereinafter the Constitution) which requires a wider interpretation of who may be afforded the right to fair labour practices.
Keywords: Illegal workers; Immigrants; Sex Workers; Unfair dismissal

The rights and duties of parties to liability insurance contracts at claim stage - Ntuli, Bonginkosi (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Insurance claims; Insurance policies

Business rescue: a delay tactic for liquidation? - Nxumalo, Misiwe Mpilenhle (University of KwaZulu-Natal, 2019)
No abstract provided.
Keywords: Business rescue; Company creditors; Company law; Liquidation; Shareholders

The possible impact of the Hague Convention on the recognition and enforcement of foreign judgments in civil or commercial matters on private international law in common-law West Africa - Okorley, Solomon (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Article 6.8 and Annex II of the WTO agreement on antidumping - Persoz, Dimitri (European University Institute, 2019)
Article 6.8 of the Antidumping Agreement (AD) allows domestic investigating authorities to make determinations on the basis of the best information available (BIA) when any interested party does not cooperate during an antidumping investigation under the discipline of Annex II of the AD. Since its introduction, this provision has been the source of extensive and neverending litigation in front of both domestic investigating authorities and the Dispute Settlement Body. In this thesis, we research to what extent the findings of the Panels and the Appellate Body regarding Article 6.8 AD are consistent with the mandate set out in Articles 3.2, 11 DSU and 17.6 AD and to what extent they are reasonable from an economic perspective. To answer the first question, we first discuss Articles 3.2, 11 DSU and 17.6 AD to establish what is the mandate of the Panels and the Appellate Body under the Dispute Settlement Body. We then examine the findings of the Panels and the Appellate Body in the interpretation of the seven terms of Article 6.8 AD under the previously established mandate. To answer the second question, we summarize the latest developments in the economic theory of adjudication and litigation. We then discuss the findings of the Panels and the Appellate Body using this economic standard. In the conclusion, we compare the results of our analysis with current negotiations on Article 6.8 AD in the Doha Round framework and further discuss the opportunity to create a single united international investigating authority.

The position of a director in South African Law : is it worth the risk - Raselo, Moeketsi Thebe (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Role of Alternative Dispute Resolution as a Mechanism for Administration of Justice - Renu, Shailja Chauhan (International Journal of Science and Research (IJSR), 2019)
Desire for quick and affordable justice is universal. Right to speedy trial is a right to life and personal liberty of every citizen guaranteed under Article 21 of the Constitution, which ensures just, fair and reasonable procedure. Alternative Dispute Resolution mechanisms have become more crucial for businesses operating in India as well as those doing businesses with Indian firms. There are various reasons for which ADR is preferred over the conventional way of resolving the disputes. India being a developing country, going through major economic reforms within the framework of the rule of law, for expeditious resolution of disputes and lessening the burden on the courts, alternative mechanisms for resolution (ADR) are the only alternative through arbitration, conciliation, mediation and negotiation.

Exemption clauses : contractual exclusion of delictual damages - Sande, Janet (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

Emerging Issues in Arbitration, Mediation and Conciliation - Sunil, Bhawna Bhelly (International Journal of Science and Research, 2019)
The resolution of disputes through alternative dispute resolution mechanisms has gained momentum over recent decades. It has increasingly occupied space in the academic literature as the “new” method to achieve “justice” for disputing parties. It is important to note that a variety of definitions of “justice” can be relied upon. However, in many cases, justice will mean the parties being able to resolve their dispute fairly, justly and amicably by applying law or legal principles. Traditional legal mechanisms for resolving disputes have been increasingly questioned as to whether they are actually capable of achieving justice in individual cases. Resolution in the courts is not only the method of resolving disputes . If the parties can resolve their own disputes then there will arise no need for court system in world. All though court system is good and fair way of dealing with civil disputes yet it might not be the best method to resolve the disputes. Basically there are four ways to of alternate dispute resolution. They are Negotiation, Mediation, Conciliation and Arbitration . The of ADR is to resolve the matters in a cost effective manner and foster long term relationship.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; MARD; Mediación; Mediation; Mediação; Médiation; Méthodes alternatives de règlement de conflit

An appraisal of the implementation of the retail distribution review's recommendations - Wilkins, Chanel (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Determining the proper law of an International Funds Transfer - Yeboah, Abena Takyiwa (University of Johannesburg, 2019)
There are many ways of making payments. One of the available options for parties to international commercial transactions is international funds transfers. These transfers occur across borders and so, raise conflict of law issues. There are some laws known internationally that regulate international funds transfers. These laws include the UNCITRAL Model Law on International Credit Transfers (no country has ratified it), article 4A of the Uniform Commercial Code and the Rome I Regulation. There are diverse ways in determining which law applies to an international funds transfer. This is done either by assessing the transaction as a single transfer or as a set of linked transactions. In African countries like Ghana and South Africa, there is a gap in the approach of the law in addressing the conflict of laws issues regarding international funds transfers. This dissertation addresses the gap in these legal regimes using the present private international law as a guide. Additionally, the present legislation and legal jurisprudence are analysed, and suggestions are given as to its improvement. This author also advocates for a legislation that adequately addresses the issues raised by transnational funds transfers in these countries. Conclusively, this will promote a predictable approach in determining the applicable law in transnational funds transfers.
Keywords: Fund transfer; Transfert de fonds; Transfert international